Using theatre as an arts-based knowledge translation strategy for health-related information: a scoping review protocol. Issue 10 (30th October 2019) - Hall, Amanda; Furlong, Bradley; Pike, Andrea; Logan, Gabrielle; Lawrence, Rebecca; Ryan, Alexandra; Etchegary, Holly; Hennessey, Todd; Toomey, Elaine
Abstract : Introduction: Substantial delays in translating evidence to practice mean that many beneficial and vital advances in medical care are not being used in a timely manner. Traditional knowledge translation (KT) strategies have tended to target academics by disseminating findings in academic journals and at scientific conferences. Alternative strategies, such as theatre-based KT, appear to be effective at targeting broader audiences. The purpose of this scoping review is to collate and understand the current state of science on the use of theatre as a KT strategy. This will allow us to identify gaps in literature, determine the need for a systematic review and develop additional research questions to advance the field. Methods and analysis: This review will follow established scoping review methods outlined by Arksey and O'Malley in conjunction with enhanced recommendations made by Levac et al . The search strategy, guided by an experienced librarian, will be conducted in PubMed, CINHAL and OVID. Study selection will consist of three stages: (1) initial title and abstract scan by one author to remove irrelevant articles and create a shortlist for double screening, (2) title and abstract scan by two authors, and (3) full-text review by two authors. Included studies will report specifically on the use of theatre as means of KT of health-related information to any target population. Two reviewers will independently extract and chart the data using a standardised data extraction form. Descriptive statistics will be used to produce numerical summaries related to study characteristics, KT strategy characteristics and evaluation characteristics. For those studies that included an evaluation of the theatre production as a KT strategy, we will synthesise the data according to outcome. Ethics and dissemination: Ethical approval was not required for this study. Results will be published in relevant journals, presented at conferences and distributed via social media.